Academic Supervision in Improving Teacher Performance in Learning at SMA Negeri 1 Teunom Aceh Jaya - Abu Bakar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the implementation of academic supervision in improving teacher performance in learning at SMA Negeri 1 Teunom, Aceh Jaya. The research focuses on: (1) academic supervision planning; (2) implementation of academic supervision; (3) evaluation of academic supervision; (4) obstacles encountered; and (5) follow-up actions of academic supervision. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, participatory observation, and document analysis. Research subjects included the principal, the vice principal for curriculum, and subject teachers. Data analysis used the Miles and Huberman model, namely data reduction, data display, and conclusion drawing. The findings reveal that: (1) Supervision planning is carried out systematically through annual program preparation, scheduling, target determination, and preparation of observation instruments based on teacher needs analysis; (2) Supervision is implemented through direct classroom observation and reflective discussions that are collaborative and democratic, motivating teachers to improve their performance; (3) Supervision evaluation is conducted continuously through result reports containing teachers' strengths and weaknesses as a basis for further guidance; (4) Main obstacles include the principal's limited time, some teachers' discomfort with supervision, and limited learning technology resources; (5) Follow-up is carried out through individual and collective coaching which has a positive impact on improving the quality of learning tools. Overall, academic supervision at SMA Negeri 1 Teunom has positively contributed to improving teacher performance, although strengthening of teachers' competency in utilizing learning technology is still needed.